Vaccination with recombinant modified vaccinia virus Ankara prevents the onset of intestinal allergy in mice. Issue 8 (30th July 2013) - Bohnen, C.; Wangorsch, A.; Schülke, S.; Nakajima‐Adachi, H.; Hachimura, S.; Burggraf, M.; Süzer, Y.; Schwantes, A.; Sutter, G.; Waibler, Z.; Reese, G.; Toda, M.; et al.
Abstract: Background: Modified vaccinia virus Ankara (MVA)‐encoding antigens are considered as safe vaccine candidates for various infectious diseases in humans. Here, we investigated the immune‐modulating properties of MVA‐encoding ovalbumin (MVA‐OVA) on the allergen‐specific immune response. Methods: The immune‐modulating properties of MVA‐OVA were investigated using GM‐CSF‐differentiated BMDCs from C57BL/6 mice. OVA expression upon MVA‐OVA infection of BMDCs was monitored. Activation and maturation markers on viable MVA‐OVA‐infected mDCs were analyzed by flow cytometry. Secretion of INF‐γ, IL‐2, and IL‐10 was determined in a co‐culture of BMDCs infected with wtMVA or MVA‐OVA and OVA‐specific OT‐I CD8 + and OT‐II CD4 + T cells. BALB/c mice were vaccinated with wtMVA, MVA‐OVA, or PBS, sensitized to OVA/alum and challenged with a diet containing chicken egg white. OVA‐specific IgE, IgG1, and IgG2a and cytokine secretion from mesenteric lymph node (MLN) cells were analyzed. Body weight, body temperature, food uptake, intestinal inflammation, and health condition of mice were monitored. Results: Infection with wtMVA and MVA‐OVA induced comparable activation of mDCs. MVA‐OVA‐infected BMDCs expressed OVA and induced enhanced IFN‐γ and IL‐2 secretion from OVA‐specific CD8 + T cells in comparison with OVA, wtMVA, or OVA plus wtMVA. Prophylactic vaccination with MVA‐OVA significantly repressed OVA‐specific IgE, whereas OVA‐specific IgG2a was induced. MVA‐OVA vaccination suppressed TH 2 cytokine production in MLN cells and prevented the onset of allergic symptoms and inflammation in a mouse model of OVA‐induced intestinal allergy. Conclusion: Modified vaccinia virus Ankara‐ovalbumin (MVA‐OVA) vaccination induces a strong OVA‐specific TH 1‐ immune response, likely mediated by the induction of IFN‐γ and IgG2a. Finally, MVA‐based vaccines need to be evaluated for their therapeutic potential in established allergy models.